Finite element modeling of reactive liquid silicon infiltration. Issue 2 (February 2020) - Hofbauer, Peter Josef; Raether, Friedrich; Rädlein, Edda
Abstract: The LSI process, i.e. the infiltration of molten silicon into porous structures, is one of the most economical techniques for the production of C/C-SiC and C/SiC ceramics. However, despite decades of development, the infiltration behavior affected by phenomena at the infiltration front has not been understood sufficiently. In the present work, a numerical model, based on the finite element method, was developed to simulate the infiltration process. The 3D model includes the penetration of silicon into the porous preform as well as the exothermal reactions at the infiltration front caused by the growth of SiC layers. For model validation, a special measuring furnace was used, enabling in situ optical inspection and weight measurement during liquid silicon infiltration into C/C-preforms in a controlled atmosphere. For the first time, a numerical model could be established which provides a tool to simulate the infiltration kinetics as well as the thermal processes during the LSI process in three dimensions. The model enables the optimization of melt infiltration processes with complex components within reasonable computer times.